Resuscitation of the Helicobacter pylori Coccoid Forms by Resuscitation Promoter Factor Obtained from Micrococcus Luteus - Aktas, Didem; Bagirova, Melahat; Allahverdiyev, Adil M.; Abamor, Emrah Sefik; Safarov, Tural; Kocazeybek, Bekir S. (SPRINGER, 2020)
Helicobacter pylori is a gram negative, spiral-shaped, and microaerophilic bacteria which can cause life-threatening diseases. It is known that more than 55% of the human population in the world is already infected by this bacterium. The traditional treatment of H. pylori infection consists of a combination of two or more antibiotics. However, H. pylori has evolved to turning its shape from spiral to coccoid form in the presence of antibiotics and this decreases the therapeutic efficacies of conventional antibiotic applications. Resuscitation promoter factor (RPF) is a protein secreted by Micrococcus luteus have significant resuscitation effects on some bacteria especially in the group of viable but non-culturable (VBNC) pathogens. However, there is no study in the literature investigating the resuscitation effects of RPF derived from M. luteus on H. pylori in order to change its form from coccoid to spiral. The purpose of this study is to investigate the resuscitation effect of RPF-containing metabolites isolated from M. luteus on the morphological transformation of H. pylori coccoid forms to spiral forms in order to increase their susceptibilities to antibiotic treatments. Rpf-containing metabolites were primarily obtained from M. luteus culture supernatants. H. pylori was exposed to five different conditions such as prolonged culture, incubation at + 4 degrees C, incubation at + 22 degrees C, cultivation in PBS and treatment with kanamycin in order to induce transformations of bacteria to coccoid forms. Induced H.pylori coccoids were characterized by inverted microscope, UV spectrophotometer, SEM imaging, and flow-cytometer. As a result, it was found that the most suitable condition for inducing coccoid forms was cultivation of bacteria with kanamycin. Followingly, different concentrations of RPF-containing metabolites were applied on H. pylori coccoids induced by kanamycin. For the first time in this study, it was determined that the Rpf-containing metabolites obtained from M. luteus demonstrated very high resuscitation effect on kanamycin-induced H. pylori coccoid forms. This new approach for resuscitation of H. pylori coccoids is thought to play an important role in increasing the treatment effectiveness of the conventional antibiotics against the infection.
Keywords: CULTURABLE STATE; IN-VITRO; WATER; GROWTH; VIABILITY; RPF; STARVATION; CONVERSION; INFECTION; GENE; Microbiology